CANCEL CULTURE SEBAGAI RESPONS MASYARAKAT TERHADAP PELAKU KASUS PERSELINGKUHAN : KAJIAN PADA AKUN INSTAGRAM @ARAWINDAK - Jehovani Ratna Mourina, Stella; Lukmantoro, Triyono; Naryoso, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The cancel culture phenomenon emerges as a form of public rejection of public figures who behave deviantly. The research aims to understand the cancel culture phenomenon and various related actions by examining the cancel culture phenomenon that occurred to an actress involved in an affair, Arawinda Kirana. Arawinda Kirana is a newcomer actress whose name began to be recognized by the public through the movie Yuni (2021). In the film Arawinda Kirana plays the role of Yuni, through which Arawinda Kirana received awards, one of which was the winner of the 2021 Citra Cup in the category of Most Favorite Female Lead Actress, she is also known for creating the hashtag #BerkainBersama, a movement that invites young people to preserve and use kebaya, and she is familiarly known to the public as